Affordable Housing Crisis or Shortage?: Reconciling Legal Scholarship with Free Market Solutions Over the Use of Eminent Domain for Economic Development - Cosgrove, Anthony W. (Journal of Law and Commerce, 2019)
Throughout the United States, low-income families are having an increasingly difficult time finding an affordable place to live.[1] Due to high rents, static incomes, and a shortage of housing, local communities, particularly in urban areas, are struggling to fight off this wave of decline and displacement.[2] Currently in the U.S., an estimated 12 million families are now spending more than half of their income on rent.[3] According to Federal Guidelines, “[f]amilies who pay more than 30 percent of their income for housing are considered cost burdened and may have difficulty affording necessities such as food, clothing, transportation, and medical care.”[4] A large reason for this overspending by low-income families is that the supply of affordable housing is shrinking.[5] Landlords and tenants both are adding to the affordable housing problem as “all sides are being squeezed.”[6] Today, most new construction on rental housing is for the high-end market, “not for low and middle-income families.”[7] So while the problem is clear, the cause of the problem is anything but. This note seeks a better understanding of the current housing problems plaguing local communities around the United States. Whether it is attributable to a crisis of societal construction or a shortage in the supply of affordable housing, this note attempts to reconcile current legal scholarship on local government initiatives, and